2007
DOI: 10.2353/ajpath.2007.060391
|View full text |Cite
|
Sign up to set email alerts
|

Aryl Hydrocarbon Receptor-Deficient Mice Develop Heightened Inflammatory Responses to Cigarette Smoke and Endotoxin Associated with Rapid Loss of the Nuclear Factor-κB Component RelB

Abstract: The transcription factor aryl hydrocarbon receptor (AhR) plays an important role in the response to environmental pollutants. However, its role in normal physiology is unclear. To investigate the role of AhR in acute lung inflammation, control and AhR knockout (KO) mice were exposed to inhaled cigarette smoke or bacterial endotoxin. Smoke-induced lung inflammation was twofold to threefold more severe in AhR KO mice than controls. Intriguingly, levels of tumor necrosis factor-alpha and interleukin-6 in the bron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
177
0
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 163 publications
(193 citation statements)
references
References 61 publications
13
177
0
3
Order By: Relevance
“…Our published studies based on an AhRdeficient mouse model indicated that a functional AhR is critical for the proinflammatory events mediated by coplanar PCBs in the vascular endothelium . Other in vivo studies with AhR knockout mice also demonstrated that AhR activation is involved in the inflammatory response induced by the AhR ligands (Thatcher et al, 2007).…”
Section: Discussionmentioning
confidence: 95%
“…Our published studies based on an AhRdeficient mouse model indicated that a functional AhR is critical for the proinflammatory events mediated by coplanar PCBs in the vascular endothelium . Other in vivo studies with AhR knockout mice also demonstrated that AhR activation is involved in the inflammatory response induced by the AhR ligands (Thatcher et al, 2007).…”
Section: Discussionmentioning
confidence: 95%
“…Transgenic mice constitutively expressing the active form of Ahr in keratinocytes develop an inflammatory skin disease characterized by atopic dermatitis in the absence of an exogenous stimulus. 19 However, Ahr knockout mice developed greater acute inflammation in lung compared to control mice in response to inhaled endotoxin and to cigarette smoke 20 . These apparently contrasting results, with either constitutive upregulation or depletion of Ahr resulting in increased inflammation, might be explained by different regulatory mechanisms of Ahr.…”
Section: Resultsmentioning
confidence: 99%
“…These apparently contrasting results, with either constitutive upregulation or depletion of Ahr resulting in increased inflammation, might be explained by different regulatory mechanisms of Ahr. Indeed, Ahr appears to produce ligandindependent inflammatory reactions, 19,20 as well as immune responses that depend on specific ligands, thus regulating the reciprocally related differentiation of T regulatory (T reg ) and proinflammatory (T H 17) T cells 21 . Because the Ahr functional polymorphism segregated in AIRmax and AIRmin mice that have been phenotypically selected by an acute inflammatory agent (polyacrylamide beads) that does not require metabolism and that does not bind to the Ahr protein, our results suggest that Ahr affects inflammatory response in an exogenous ligand-independent way.…”
Section: Resultsmentioning
confidence: 99%
“…Smoke was generated using 3R4F reference cigarettes (University of Kentucky Reference Cigarette Program) smoked according to the Federal Trade Commission protocol (1 puff per minute of 35-mL volume per cigarette) and diluted with filtered room air using a Baumgartner-Jaeger CSM2072i automated smoking machine (CH Technologies, Westwood, NJ) as previously described. 11,16 The number of cigarettes loaded in the carousel and the flow rate of dilution air were adjusted to give a nominal smoke exposure of 250 mg/m 3 total particulate matter; the mean concentration of these exposures was 265 AE 48 mg/m 3 . Control animals were exposed to filtered room air.…”
Section: Exposure To Cigarette Smoke and Rvd1 Treatment Regimenmentioning
confidence: 99%